2023
DOI: 10.1200/go.21.00289
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Oral Anticancer Medications Among Women With Breast Cancer in Africa: A Scoping Review

Abstract: PURPOSE Oral anticancer medications (OAMs) improve treatment outcomes and survival in women with breast cancer (BC). However, adherence to OAM therapy remains suboptimal. This scoping review provides evidence of adherence to OAMs among African women with BC. METHODS We searched four databases and gray literature, using guidance from the Joanna Briggs Institute. Thirteen studies on adherence rates, determinants, and interventions were included. NVivo 12 software was used to perform thematic analysis of the incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
(155 reference statements)
0
3
0
Order By: Relevance
“…The significant barriers identified were Islamic religion, comorbidities, mastectomy, anastrozole treatment, side-effects, unawareness of medical insurance coverage, and seeking treatment from traditional healers. 46 The African Breast Cancer–Disparities in Outcomes prospective cohort study conducted in sub-Saharan Africa reported that surgery with multimodality treatment was initiated in only a minority of patients with localized BC, and a majority of women did not complete local or systemic therapy as indicated clinically. 47 Such important statistics are unfortunately not available from many areas of the world.…”
Section: Socioeconomic Disparities and Adherence To Therapymentioning
confidence: 99%
“…The significant barriers identified were Islamic religion, comorbidities, mastectomy, anastrozole treatment, side-effects, unawareness of medical insurance coverage, and seeking treatment from traditional healers. 46 The African Breast Cancer–Disparities in Outcomes prospective cohort study conducted in sub-Saharan Africa reported that surgery with multimodality treatment was initiated in only a minority of patients with localized BC, and a majority of women did not complete local or systemic therapy as indicated clinically. 47 Such important statistics are unfortunately not available from many areas of the world.…”
Section: Socioeconomic Disparities and Adherence To Therapymentioning
confidence: 99%
“…Culture is known to partly shape health attributions, health beliefs and health behaviours, leading to a diversity in belief systems about healing among cultural groups. 13 Cultural background also informs beliefs about medication, such as beliefs about the benefits and dangers of medicines, 14 drug efficacy, 15 and affects behaviours, such as, adherence to medication 15 , 16 , 17 including prescription drugs. 18 Religious concerns has had a long history 19 and can lead to discontinuation of medication, when medicine components are considered prohibited, 20 such as certain animal-derived products, 21 or during observances such as the Ramadan fasting period.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The common modalities for breast cancer treatment include surgery, chemotherapy and radiotherapy. 3 Traditional chemotherapy has mainly been administered intravenously when the patient presents to an outpatient infusion centre or The review 23 revealed that few observational studies from Nigeria [26][27][28] assessed factors influencing adherence to OAMs among women with BC. Financial difficulties, medication costs, younger age, and feeling well after starting chemotherapy contributed to poor adherence to OAMs.…”
Section: Introductionmentioning
confidence: 99%